The Implementation of Cooperative Learning Approach with Multimedia for Children’s Literature Learning at Elementary School in the Characters Building Perspective - Rukayah Rukayah; Y Slamet; Andayani Andayani (International Journal of Pedagogy and Teacher Education, 2018)
The purposes of this study were (1) finding the effectiveness of cooperative learning approach with multimedia for children’s literature learning at elementary school; and (2) describes the acceptability of collaborative learning approach with multimedia for children’s literature learning at elementary school based on the stakeholders’ opinions. The method used is quasi-experimental research. The study location includes six elementary schools in Central Java, Indonesia. The data sources this study includes (1) the informant; (2) events, namely the children’s literature learning activities in fourth and fifth  grade of elementary school where studied; (3) the document, in the form of syllabi, lesson plans, and other relevant documents; and (4) test results. The samples size is 161 students. The data validity used correlation point biserial, and reliability data was used KR-20 formula. The data analysis technique used ANOVA. The research results showed that 1) Fcount on fourth grade was 22.141 with Ftable is 3.91. Then, Fcount in fifth grade was 11.380 with Ftable is 3.91. There are mean that children’s literature learning result which is resulted from a cooperative learning approach with multimedia is better than conventional approach, and (2) children’s literature learning model with cooperative learning approach with multimedia in elementary school and “Guidelines for Children’s Literature Learning within Cooperative Learning Approach in Elementary School” can be accepted by stakeholders. The conclusion of this research is children’s literacy learning in elementary used cooperative learning approach with multimedia can improve the quality of learning processes and children’s literature teaching result, both from the aspect of cognitive, affective, and psychomotor. Besides, that can be said the children’s literacy learning in elementary school can be used to improve the supreme nature, moral education and the development of national character values.